Plasmon based biosensor for distinguishing different peptides mutation states - Das, Gobind (Nature Publishing Group, 2013)
Periodic and reproducible gold nanocuboids with various matrix dimensions and with different inter-particle gaps were fabricated by means of top-down technique. Rhodamine 6G was used as a probe molecule to optimize the design and the fabrication of the cuboid nanostructures. The electric field distribution for the nanocuboids with varying matrix dimensions/inter-particle gap was also investigated. These SERS devices were employed as biosensors through the investigation of both myoglobin and wild/mutated peptides. The results demonstrate the probing and the screening of wild/mutated BRCA1 peptides, thus opening a path for the fabrication of simple and cheap SERS device capable of early detection of several diseases.